Strategi Pengembangan Pariwisata Pada Museum Raja Ali Haji - Wathani, Muhammad Imadil; Melisa, Yolada; Al Hafis, Alip Irpan (Journal of Tourism Sciences, Technology and Industry, 2023)
The results showed that applicable strategies include collection diversification, improvement of infrastructure, promotion through social media, and development of educational tour packages. In conclusion, the implementation of these strategies is expected to increase the number of visitors and advance tourism at the Raja Ali Haji Museum. Good museum management and adaptation to current events can have a positive effect on photos and tourist visits. The Raja Ali Haji Museum has many historical collections and has great historical value. Therefore, a development plan is needed to deal with the increase in tourist visits. This research seeks to create a development plan for the Raja Ali Haji Museum by increasing tourist visits based on the characteristics of the museum. This research uses a descriptive method by organizing the results of observation data, interviews, documentary studies and previous literature. The evaluation was carried out through direct observation of many things, including the tourist attraction of the Raja Ali Haji Museum and other heritage sites, the location of the museum and the management of the museum. The Raja Ali Haji Museum development plan may include image creation, museum profile creation, beautiful merchandise and special souvenirs, promotions on websites and social media, collaboration with travel groups and collaboration with educational institutions. By implementing this development strategy, it is hoped that the Raja Ali Haji Batam Museum will become a center of education, inspiration and pride for the local community and visitors from various backgrounds, making this museum a developing and sustainable cultural destination.